A Multi-Resolution Sequence Method with Strong Constraints for Marine Gravity Matching Navigation - Ning Mao; An Li; Jiangning Xu; Fangjun Qin (Journal of Marine Science and Engineering)
The navigation and positioning of underwater vehicles is challenging work, especially when there is already a large initial position error, and there is an increasing concern about how to quickly correct the position error. To enhance positioning accuracy under large initial positioning errors, this paper proposes a multi-resolution sequence method with a strong constraint marine gravity-matching navigation algorithm and validates it through field experiments. First, the fundamental principles and common optimization approaches of the standard Terrain Contour Matching (TERCOM) and Iterative Closest Contour Point (ICCP) algorithms are introduced, the limitations of the sequence-matching algorithms are analyzed, and a multi-resolution sequence-matching fusion framework is designed. Then, the constrained models incorporating positional, navigational, and gravitational parameters are designed, and a strongly constrained multi-resolution sequence-matching algorithm is proposed. Finally, the performance of the method is verified by three field test trajectories with an initial position error of about 6 nautical miles. The field test results show that the proposed method has better accuracy and reliability under large initial position errors.